A Thematic Inquiry into the Burnout Experience of Australian Solo-Practicing Clinical Psychologists - Hammond, Trent E.; Crowther, Andrew; Drummond, Sally (Frontiers in Psychology, 2018)
Objective: Burnout is conceptualized as a syndrome that consists of emotional exhaustion, depersonalization, and decreased personal accomplishment. Despite the increased frequency and severity of burnout in the Western world, there is limited published research regarding the experiences of clinical psychologists who have had burnout. The present study examines clinical psychologists’ different experiences of burnout in Australia. Design and methods: In the year 2015, six privately practicing and solo-employed clinical psychologists provided rich qualitative data by participating in semi-structured interviews. Thematic analysis was the method used to analyze clinical psychologists’ natural accounts of their burnout experiences. Using NVivo, emerging themes were identified through coding ‘first order constructs’ and then axial code ‘second order constructs.’ Findings: Clinical psychologists experienced a diverse range of symptoms, including the enduring effects of burnout, mental stress, fatigue, decreased personal accomplishment, negative affect, depersonalization, reduced productivity and motivation, and insomnia. They identified precursors of burnout, including excessive workload and hours of work, life stressors, mismanaged workload, and transference. Clinical psychologists suggested that protective factors of burnout include knowledge and years worked in direct care, and trusting and long-term relationships. They indicated that the barriers to overcoming burnout include the fallacy that their clients’ expectations and needs are more important than their own, the financial cost of working in private practice, contemporary knowledge and inadequate education regarding self-care, and time constraints. Discussion and conclusions: The findings presented in this study provide psychologists and other health professionals with an insight about the burnout experience and inform professionals of the mental shortcomings of working as a solo-practicing clinical psychologist. Findings from this study should lead to an increased understanding of the complexities of burnout, and ultimately reduced cases of burnout, absenteeism, and staff disengagement.